The Distribution of Diagnostically Acceptable Distortions in Panoramic Radiographs: A Retrospective Study at the Dental Hospital of Universitas Syiah Kuala : Diagnostically Acceptable Distortions in Panoramic Radiographs - Kemala Hayati; Liza Meutia Sari; Niswa Ajilla; Ridha Andayani; Afrina Afrina; Citra Feriana Putri (Journal of Syiah Kuala Dentistry Society, 2026)
Panoramic radiography is one of the most widely used extraoral imaging modalities in dentistry. Producing high-quality panoramic radiographs is essential for accurate diagnosis and treatment planning. However, distortions caused by equipment preparation, patient preparation, and patient positioning may compromise image quality while still meeting diagnostically acceptable criteria. This study aimed to describe the distribution of distortions in diagnostically acceptable panoramic radiographs obtained at the Radiology Unit of the Dental Hospital, Faculty of Dentistry, Universitas Syiah Kuala, Banda Aceh, using retrospective data collected between January 2023 and August 2024. A descriptive observational study with a cross-sectional design was conducted using retrospective data. A total of 435 panoramic radiographs that fulfilled the inclusion criteria were evaluated. Distortions were identified and classified into three categories: equipment preparation, patient preparation, and patient positioning. Descriptive statistical analysis was performed to determine the frequency and percentage of each distortion type. A total of 1,305 distortions were identified across 435 panoramic radiographs. Patient positioning errors accounted for the vast majority of distortions (96.78%), followed by equipment preparation errors (2.91%) and patient preparation errors (0.31%). The most frequently observed distortion was improper tongue positioning (25.59%), followed by failure to close the lips around the bite-block (21.38%) and anteroposterior positioning errors (17.70%). Distortions in diagnostically acceptable panoramic radiographs remain common, with patient positioning errors representing the predominant source of image distortion. These findings highlight the importance of continuous operator training and improved patient instructions to minimize positioning errors and enhance panoramic image quality for diagnostic purposes.